Recycling and Its Effects on the Environment - Nodoushani, Omid; Stewart, Carol; Kaur, Manpreet (Competition Forum, 2016)
Consumers and businesses have an ethical obligation to do their part to reuse or recycle unwanted items. However, while some consumers and businesses do reuse or recycle e-waste, glass, metal, plastic, paper or textiles, more could be done. Even with environmentalists warning of potential chemical hazards these items produce in landfills, an estimated 85 percent of landfills are filled with unwanted waste. The recycling industry along with local government run media campaigns to raise awareness; however, as a result consumers and businesses may be experiencing information overload which may have a negative impact on consumers ' recycling efforts.
Keywords: Communication; Consumers; Consumption; Electronic waste; Electronics; Energy consumption; Environmental impact; Environmental protection; Environmentalists; Greenhouse gases; Information overload; Landfill; Natural resources; Plastics; Raw materials; Recycling; Textiles; dept.mgt

Boosting Performance on an Evaluative Math Test: Goal Activation vs Self-Affirmation - Wieland, Alice M.; Burnham, Thomas A. (Psychological Reports, 2016)
This study compared the effectiveness of goal activation versus self-affirmation and a control condition as interventions for increasing performance on an evaluative task (a difficult math test; N = 78; M age = 20.3 yr., SD = 1.9). Although there has been much recent literature on the effects of activating goals, the existing literature does not examine possible spillover effects of activating goals on performance tasks. Results indicated that goal activation resulted in significant performance enhancements over both the self-affirmation and control conditions, while self-affirmation did not improve performance significantly relative to the control condition. Additionally, interest in the task, as a cue for self-regulatory resources, mediated the effect of goal activation on increased performance.
Keywords: dept.mgt

Time horizon of investments in the resource allocation process: review and framework for next steps - Reilly, Greg; Souder, David; Ranucci, Rebecca (Journal of Management, 2016)
Corporate investment inherently relies on time horizon, as profits result from acquiring assets or developing capabilities that yield future benefits that exceed upfront costs. Despite the importance of time horizon to understanding resource allocation, knowledge about the subject has accumulated slowly. Our review therefore encompasses insights from several research streams that partially address the subject even though time horizon is not the central construct in any of them. We aim to clarify key constructs related to time horizon, organize prior research about the antecedents of time horizon, explain the implications of several theoretical traditions for time horizon, and detail the range of measures that have been used to capture time horizon empirically. By focusing narrowly on this topic but searching broadly for references, we provide integrative summaries of existing research and identify opportunities for new and unique research.
Keywords: behavioral strategy; decision making; dept.mgt; resource allocation/management

Mindfulness meditation and art appreciation as meaning-making practices - Yang, Charlie (Academy of Management, 2016)
Mindfulness has recently gained significant attention and momentum in academia and popular culture. There is, however, a paucity of literature on how students make sense of contemplative practices. This paper proposes that mindfulness meditation is not merely a useful tool for stress reduction, but also a metacognitive meaning-making practice.
Keywords: Art appreciations; Contemplative practice; Meaning makings; Metacognitives; Popular cultures; Stress reduction; dept.mgt